Lateral Rectangular Flap for Augmenting Vermilion Deficiency in Unilateral Cleft Lip Repair - Rafeeq, Hemin Himdad; Fattah, Jalal Hamasalih (South Eastern European Journal of Public Health, 2024)
Background and Objective: Cleft lip and palate are common congenital anomalies that require precise management with main component of repairing lip is the aesthetic outcome. Using lateral rectangular flap is a new method to optimize the medial vermilion deficiency. The goal of this study is to evaluate the efficacy of lateral rectangular flap for augmenting medial vermilion deficiency in unilateral cleft lip repair. Methods: This is a clinical trial was conducted in Rizgary Teaching Hospital and several private hospitals in Erbil, Iraqi Kurdistan Region from June 2021 to June 2023. A total of 18 patients with unilateral, complete and incomplete, isolated cleft lip and cleft lip and palate were included. Preoperative and postoperative photos were documented. Outcomes were analyzed up to one year following the repair. Results: The included patients had either isolated cleft lip (44.4%) or cleft lip and palate (55.6%). Cleft side was right (38.9%) or left (61.1%). Cleft was incomplete in only 2 patients (11.1%) and complete in 16 patients (88.9.%). No early postoperative complications were reported; however 5 patients complained of scar later after surgery. Outcome evaluation score for Cubid’s bow was 1 for 5 patients and 2 for 13 patients. On the other hand, score for lateral vermilion deficiency was 2 for all patients. No significant association was detected between patients’clinical data and the type of cleft. Conclusion: We found that lateral rectangular flap for augmenting medial vermilion deficiency in unilateral cleft lip repair was effective with excellent surgical outcome and minimal patients’ morbidity.